The application of the rehabilitation module for academic achievement among technical college student's of Pahang Skills Development Center - Roshasliza, Samat (2010)
Engineering graduates and technical employees are playing an increasingly significant role in the economic development of Malaysia, especially under its current national economy transformation. How to enhance their related skills has become a heated issue. This research is trying to ascertain the application of rehabilitation module known as MCBEREBT Module for academic achievement among technical college students that study at PSDC’s College. The Treatment Module consists of three techniques which is mental technique, cognitive technique and behavior technique. All the techniques complement each other in health promotion to give a better environment and condition to all technical college students such as stress reduction technique and mind-body control technique. The module facilitate the students to learn self-regulation which is later the student have the ability to control their own behavior. By establishing the MCBE-REBT (Mental, Cognitive, Behavior Technique) Module, the relationship between personality types and academic achievements has been evaluated. The personality types as a part of the module are classified by using Credo Personality Profiling, while the academic achievements are measured in terms of GPA. Also by integrating the Biofeedback Computer Game-based Training into MCBE Techniques, a rehabilitation Module is developed to help the students to learn self-regulation and relaxation technique. Result from Spearman, rs, correlation matrix of outcome measures improvement (delta changes scores) on the total sample showed that there is no significant correlation between improvement in GPA and biofeedback training as indicated by heart rate reduction. Result of Friedman test shows that the heart rate of subjects receiving biofeedback training significantly reduced from pre to post intervention (χ2 (2) = 8.667, p = 0.011).Therefore, it shows that by practicing the REBT_MECB Module the students can learn the skills of relaxation and will be ready to manage their emotions, and good in self-regulation whenever facing stress and anxiety.